Labor Inclusion in the Construction Sector: Evidence from Mexico - Tovar-García, Edgar Demetrio; Ornelas-Barajas, Luis Alfonso; Moreno Abril, Francisco (Griffith University, 2023)
This study aims to present empirical evidence demonstrating the receptiveness of construction professionals and individuals with spinal cord injuries to participate in the construction sector, challenging the prevalent belief that spinal cord injury precludes labor inclusion. Accordingly, in August 2021, this study conducted two surveys to collect data from distinct groups: builders and individuals with spinal cord injuries. The builder survey involved a representative sample of 52 respondents, drawn from a population of 322 members of the Mexican Chamber of the Construction Industry,Jalisco delegation. Simultaneously, 44 individuals with spinal cord injuries participated in the survey, sourced from a pool of 455 members affiliated with Don Bosco sobre Ruedas and Vida Independiente. The survey process facilitated a comprehensive diagnosis, identifying potential areas for enhanced inclusion within the construction sector. The empirical findings challenge conventional wisdom, indicating that a spinal cord injury does not act as a barrier to labor inclusion within the construction sector. On the contrary, the study emphasizes that having employees with disabilities can exert a positive impact on company dynamics. Moreover, the research identifies specific activities where individuals with spinal cord injuries exhibit a higher potential for inclusion, thereby redefining traditional expectations. Therefore, this study contributes to the originality of the existing discourse by providing concrete empirical evidence that counters widespread assumptions about the limitations faced by individuals with spinal cord injuries within the construction industry
Keywords: building; disability; discrimination; Labor inclusion; spinal cord injury